Tunable self-seeded multi-wavelength Brillouin-erbium fiber laser based on few-mode fiber filter - 邹辉;马雷;熊慧;张云山;刘春晓 (Optoelectronics letters, 2017)
A tunable self-seeded multi-wavelength Brillouin-erbium fiber laser（BEFL） is proposed and demonstrated based on a few-mode fiber filter（FMFF） with varying temperature. The FMFF configuration is a section of uncoated few-mode fiber（FMF） sandwiched between two up-tapers. As the temperature varies from 25 °C to 125 °C, the transmission spectrum of FMFF moves towards the longer wavelength. The self-excited Brillouin pump is internally achieved by cascaded stimulated Brillouin scattering（SBS） in the single mode fiber（SMF）. Then employing the FMFF temperature variation characteristics in the ring cavity fiber laser, the multi-wavelength of the output laser can be tuned, and the tunable range is about 8.0 nm. The generation of up to 15 Brillouin Stokes wavelengths with 16 d B optical signal-to-noise ratio（OSNR） is realized.